Activation of SphK2 contributes to adipocyte-induced EOC cell proliferation - Dai Lan; Wang Chen; Wang Wenjing; Song Keqi; Ye Taiyang; Zhu Jie; Di Wen (Open Medicine, 2022)
Epithelial ovarian cancer (EOC) is the leading cause of deaths due to cancer in women. Adipocytes have been suggested to play a key role in the stimulation of EOC growth. However, the mechanisms underlying the adipocyte-induced EOC proliferation remain undefined. Here, we provide the first evidence that adipocytes induce the activation of sphingosine kinase (SphK) 2 in EOC, which represents a novel pathway that mediates the adipocyte-induced EOC growth. SphK2 inhibition in EOC cells led to a remarkable inhibition of the adipocyte-induced cell proliferation. Moreover, the adipocyte-induced SphK2 activation in EOC cells was extracellular signal-regulated protein kinases (ERK) dependent. Furthermore, silencing SphK2 in EOC significantly inhibited the adipocyte-induced expression of phospho-ERK and c-Myc, two crucial players in EOC growth. Collectively, the current study unraveled a previously unrecognized role of SphK2 in the adipocyte-induced growth-promoting action in EOC, suggesting a novel target for EOC treatment.